Ana Castillo in search of herstory - Gondor-Wiercioch, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper discusses four novels by Chicana writer Ana Castillo, ?The Mixquiahuala Letters?, ?Sapogonia?, ?So Far From God? and ?The Guardians? which demonstrate gradual change in the autor`s position from a supporter of the radical feminism towards an advocate of moderate feminism .
Keywords: Castillo, Ana (1953- ); Chicana literature; feminism; herstory; Latina representation; border studies; Mestizo myths